Green Revitalization of the NZS Square in Bialystok - Tokajuk, Andrzej (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2024)
This article presents the results of research conducted at the Faculty of Architecture of the Bialystok University of Technology by a team consisting of: Dr Eng. Arch. Andrzej Tokajuk and student Eng. Arch. Kinga Wiśniewska in 2023−2024. The aim of the research was to develop the concept of revitalization of the NZS Square in Bialystok. As a working method, design experiment was adopted, which was preceded by a broad analysis of revitalization actions of city public spaces and the literature. As a result of the research, the concept of „green” revitalization was created, which should constitute a model for carrying out such projects in Polish cities in the 21st century.